Heracleum munzurense (Apiaceae), a new species from East Anatolia, Turkey and taxonomic position of Tetrataenium lasiopetalum - Duran, Ahmet; Lyskov, Dmitry; Samigullin, Tahir; Paksoy, Mehmet Yavuz (Phytotaxa, 2024)
A new species, Heracleum munzurense (Apiaceae), is described from East Anatolia, Turkey. It grows in damp places formation of the Munzur Mountains in the district of Pülümür (Tunceli Province). The taxonomic affinities of the new species were determined by analyzing morphological data and through a molecular phylogenetic study of nrITS/ETS. The new species is morphologically and genetically related to H. apiifolium and H. pastinaca, but differs mainly in stems, leaves, pedicels, rays and petals pubescence, petals size, fruit hairs, and size features. The anatomical structure of the fruit is given. The diagnostic morphological characters of the new species are discussed. In this study, the geographical distribution of the new species and the related taxa H. apiifolium, H. lasiopetalum, and H. pastinaca is mapped. In addition, the habitat, ecology, phenology, and conservation status of the new species are also provided. Tetrataenium lasiopetalum is also closely related to this group of species. Common morphological features and results of molecular phylogenetic study suggest to transfer this species back to the genus Heracleum.